Lexical Productive Competency, Short-Term Memory and Academic Performance in Higher Education: Correlations from a Simple and a Multivariate Analysis - Zapico, Martín Gonzalo (2017)
Talking about academic performance in higher education is to refer to a subject of great interest both terms of theoretical reflection and praxis. Given the large number of studies and the great diversity of them in the field of performance prediction, many elements that predict academic performance have been proposed. However, three of them stand out because of their statistical strength: personal motivation (self-esteem, expectations, stress), critical judgment, and performance in previous instances. The hypothesis proposed in this paper is that both lexical-productive vocabulary and working memory can be statistically valid indicators of academic performance. To confirm this hypothesis, a quantitative comparative analysis (descriptive and correlation statistics) was performed in a sample of 120 students of an institute of higher education which were administered both a test of lexical-productive vocabulary and a test of working memory. The results suggest that vocabulary is a highly reliable predictor of performance, while memory has a significantly lower degree of correlation than that of vocabulary.